ANALISIS PENGARUH CAPITAL ADEQUACY RATIO, LOAN TO DEPOSIT RATIO, BOPO, DAN NET INTEREST MARGIN TERHADAP KINERJA KEUANGAN BANK. ( Studi pada Bank Umum Konvensional yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2014 ) - Ardiansyah, Rizki; Mawardi, Wisnu (Faculty of Economics and Business Diponegoro University, 2017)
The banking industry in Indonesia facing a difficulty after the crisis and showing its performance.. This study aims to obtain empirical evidence about the effect of Capital Adequacy Ratio (CAR), Loan Deposit Ratio (LDR), Operating Expenses to Operating Income (BOPO) and Net Interest Margin (NIM) to the Return On Assets (ROA) and determine the variabel that give the dominant influence on the annual report of conventional banks in Indonesia.The object of research is 41 conventional banks in Indonesia in assets listed on the Bursa Efek Indonesia (BEI) for the period 2010-2014 and the sample used in this research is secondary data from Return On Assets (ROA). This study used the purposive sampling method. The data analyses employed the use of multiple linear regression. The result from this study indicates that CAR and NIM has not significant influences on ROA. And then, LDR and BOPO has significant influence on ROA.